Inhibition of Angiogenesis by MiR-524-5p through Suppression of AKT and ERK Activation by Targeting CXCR7 in Colon Cancer Cells. (10th November 2022) - Li, Xiang; Li, Zitao; Li, Caijuan; Fang, Yi; Zhang, Gaosen; Yan, Yudie; Zhao, Xiaodi; Song, Xiaole; Zhang, Zhen
Abstract : Increasing evidence shows that alterations in microRNA (miRNA) expression are involved in the occurrence and development of various malignant tumors, including colon cancer. MiRNA-524-5p has been reported to have anticancer activity in colon cancer. This study explored the influence of the miRNA-524-5p/CXCR7 axis on angiogenesis using colon cancer cells and further studied the mechanisms involved. We found that changing the expression of miRNA-524-5p can affect colonic proliferation, migration, and angiogenesis. Furthermore, angiogenesis induced by miRNA-524-5p overexpression was reversed by overexpression of CXCR7 in HT-29 cells, while the opposite was observed in Caco-2 cells. Furthermore, miRNA-524-5p inhibited the activation of AKT and ERK signaling by targeting CXCR7. Overall, our results indicated that the miRNA-524-5p/CXCR7 axis regulated angiogenesis in colon cancer cells through the AKT and ERK pathways.